BUILDING INFORMATION MODELING AS A TOOL FOR OPERATIONAL MANAGEMENT OF THE CONSTRUCTION PROCESS - A. Saitgaraev (Вестник университета)
In article the concept of Lean Construction is considered. Information modeling of buildings at a construction stage from the point of view of functions of management is analyzed. Ways of improvement of system of operational management of the course of construction process by means of BIM technologies within the concept of Lean Con-struction are analyzed. Besides, the scheme of operational management of the course of construction process by means of BIM model which is the effective tool of the concept Lean Construction at the expense of what the probability of implementation of the project essentially increases in time is presented in article.